Respuesta :
First you expand the brackets:
X^2+3x+2=x^2+2x-3
Take away x^2 from both sides
3x+2=2x-3
Then you get rid of the 2x from one side
x+2=-3
Take 2
x=-5
Therefore -5 is your answer to x, hope this helps
X^2+3x+2=x^2+2x-3
Take away x^2 from both sides
3x+2=2x-3
Then you get rid of the 2x from one side
x+2=-3
Take 2
x=-5
Therefore -5 is your answer to x, hope this helps
Answer: x = -5
Step-by-step explanation:
(x + 1)(x + 2) = (x + 3)(x - 1)
x² + 3x + 2 = x² + 2x - 3 Foiled both sides
3x + 2 = 2x - 3 Subtracted x² from both sides
x + 2 = - 3 Subtracted 2x from both sides
x = - 5 Subtracted 2 from both sides
Check:
(-5 + 1)(-5 + 2) = (-5 + 3)(-5 - 1)
(-4) (-3) = (-2) (-6)
12 = 12 [tex]\checkmark[/tex]